Monoceros OB4: a new association in Gaia DR2. Issue 1 (31st March 2021) - Teixeira, P S; Alves, J; Sicilia-Aguilar, A; Hacar, A; Scholz, A
ABSTRACT: We use Gaia DR2 data to survey the classic Monoceros OB1 region and look for the existence of a dispersed young population, co-moving with the cloud complex. An analysis of the distribution of proper motions reveals a 20–30 Myr association of young stars, about 300–400 pc away from the far side of the Mon OB1 complex, along the same general line of sight. We characterize the new association, Monoceros OB4, and estimate it contains between 1400 and 2500 stars, assuming a standard initial mass function, putting it on par in size with NGC 2264. We find from the internal proper motions that Mon OB4 is unbound and expanding. Our results seem to unveil a larger and more complex Monoceros star formation region, suggesting an elongated arrangement that seems to be at least 300 × 60 pc.